ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PRODUKSI HOME INDUSTRI KRIPIK TETTE DESA TARO’AN PAMEKASAN - Zaini, Moh.; Sayyidi (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2024)
The aim of this research is to determine and analyze production factors that influence the production value of the Tette chips home industry in Taro'an Village, both simultaneously and partially. There are three main production factors used in the production of tette chips home industry products in Taro'an Village consisting of raw materials, labor and capital. Capital comes from personal capital and some from group bank loans. As many as 450 village residents are directly involved as workers and part of business owners. The production process relies on human power without involving modern technology. Meanwhile, the raw material for cassava is obtained from agricultural products and markets in the surrounding area. Quantitative methods with multiple linear regression analysis are applied using primary data obtained directly from data sources to answer research problems. The results reveal that the three production factors simultaneously have a positive and significant influence of 72.6%, while the production factors partially influence production value at different levels. Consecutively, the level of influence given starts from variable X2 then X1 and X3, so that the tette chip home industry in Taro'an Pamekasan Village is important to developed.